Dietary red palm oil-supplementation offers cardioprotection against Ischaemia/Reperfusion injury : possible cellular mechanisms involved - Esterhuyse, Adriaan Johannes (Stellenbosch : University of Stellenbosch, 2011)
Dissertation (PhD)--University of Stellenbosch, 2005.